2020
DOI: 10.1002/pds.5122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence rate of hospital admissions related to medication between 2008 and 2013 in The Netherlands

Abstract: In 2009 a Dutch guideline was published containing recommendations to reduce Hospital Admissions Related to Medications (HARMs). This study aims to examine time-trends of HARMs and their potential preventability between 2008 and 2013 in The Netherlands. Methods: A retrospective prevalence study was conducted using the Dutch PHARMO Database Network. A semi-automated pre-selection was used to make a crude identification of possible HARMs of which four samples were selected. These were independently assessed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…7,8 Because of non-adherence, patients may not benefit optimally from the therapy, which may cause morbidity, mortality, hospital admissions, and increased healthcare costs. [9][10][11][12][13][14] Adherence is often perceived as the patients' responsibility, but they can be supported by informal caregivers and primary care professionals, such as professionals from the general practice (eg, clinical nurse specialist, practice nurse, and general practitioner), pharmacy (eg, pharmacy technician and pharmacist), and home care. 15 Home care in the Netherlands involves care delivered in patients' homes by nurses of different educational levels, such as registered nurses, licensed practical nurses, and nurse aides.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Because of non-adherence, patients may not benefit optimally from the therapy, which may cause morbidity, mortality, hospital admissions, and increased healthcare costs. [9][10][11][12][13][14] Adherence is often perceived as the patients' responsibility, but they can be supported by informal caregivers and primary care professionals, such as professionals from the general practice (eg, clinical nurse specialist, practice nurse, and general practitioner), pharmacy (eg, pharmacy technician and pharmacist), and home care. 15 Home care in the Netherlands involves care delivered in patients' homes by nurses of different educational levels, such as registered nurses, licensed practical nurses, and nurse aides.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies like HYVET [2] and SPRINT [3] have shown benefits of antihypertensive therapy in older patients (> 75 years) as well. Nevertheless, older patients are known to be more susceptible to Adverse Drug Events (ADEs) of antihypertensives, which increase the risk of hospital admissions [1,[4][5][6][7]. Therefore, guidelines helping to assess the benefit-risk balance for an individual patient are highly recommended [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A recent Dutch study showed that almost 20% of the potentially preventable medication related hospital admissions in older patients were a result of ADEs like syncope, dizziness and falls. These ADEs were mainly associated with the use of multiple antihypertensive medications [4][5][6]. In older patients, because of frailty and pharmacokinetic changes, these side effects may occur more frequently or may be more serious [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Older people are four times more likely to be admitted due to drug-related problems than younger adults [18,19]. It is estimated that DRAs account for 10-30% of all acute hospital admissions in older people, and about half of these are considered potentially preventable [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Older people are four times more likely to be admitted due to drug-related problems than younger adults [18,19]. It is estimated that DRAs account for 10-30% of all acute hospital admissions in older people, and about half of these are considered potentially preventable [19][20][21][22][23][24][25]. Similarly, the risk of drug-related readmissions is high in older people with an estimated incidence of 21% (IQR 14-23), although reported incidences vary greatly among studies due to heterogeneity in definitions and study populations [11,12,26].…”
Section: Introductionmentioning
confidence: 99%